Radiation Studies on the Commercial Parameters of the Tasar Silkworm, Antheraea proylei (Lepidoptera) - N. Ibotombi2, O. Premila Chanu1* and (Journal of Experimental Sciences, 2011)
Commercial parameters namely silk ratio (SR),Ã‚Â  shell weight, silk yield, effective rate of rearing (ERR), cocoon weight, double cocoon formation, formation and frequency of naked pupae etc. were studied in irradiated tasar silkworm, Antherea proylei. The silk parameters were found to be decreasing as the dose is increased, but at low doses vigor is obtained as in treatment with 200 Gy in IVth instar.